Diffraction by an impedance half-plane dependence on the impedance parameter - KUDREWICZ, H. (Archives of Acoustics, 1990)
The problem of plane wave diffraction by an impedance half-plane is considered. The aim of the paper is to analyze how the solution depends on the complex impedance parameter. The Senior solution is analytically continued from real positive values of the parameter onto the two-sheeted Riemann surface. It is shown that the result of the analytic continuation has two branch points of the first order and one pole. The pole is related to incidence angle of the plane wave. The proper choice of the branch is uniquely determined from the outgoing wave condition. Different types of surface waves excited on the impedance half-plane are also discussed.